2023
DOI: 10.1002/adfm.202214891
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking and Critical Design Considerations of Zero‐Excess Li‐Metal Batteries

Abstract: Zero-excess Li metal batteries (ZELMBs), in which a Li-anode is formed in situ during charging, have received much attention in recent years. ZELMBs bear great potential to increase energy density and facilitate battery production, thereby reducing cost as well as material and energy consumption. Practical application of ZELMBs has so far been limited by challenges related to the non-uniform deposition behavior of Li, leading to inadequate performance and safety concerns. To address these issues, promising app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…For this reason, AFLMBs are more correctly described by the name "zero excess Li-metal batteries". [18,19] Unfortunately, the real-world application of AFLMBs is mainly hindered by safety and efficiency issues. Upon cycling, Li metal unhomogenuously deposits to form Li dendrites that are known to be the cause of internal short circuits and safety concerns (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, AFLMBs are more correctly described by the name "zero excess Li-metal batteries". [18,19] Unfortunately, the real-world application of AFLMBs is mainly hindered by safety and efficiency issues. Upon cycling, Li metal unhomogenuously deposits to form Li dendrites that are known to be the cause of internal short circuits and safety concerns (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, AFLMBs are more correctly described by the name “zero excess Li‐metal batteries”. [ 18,19 ]…”
Section: Introductionmentioning
confidence: 99%
“…47 Further research has also been directed towards the use of non-planar current collectors such as patterned materials and porous media as substrates for Li deposition. 46,48–52 These concepts focus on using 3D materials that provide internal spaces for Li deposition instead of the conventionally used 2D foil substrates, potentially preventing volume and pressure fluctuation as well as Li dendrite growth. 48,50,53…”
Section: Introductionmentioning
confidence: 99%
“…24 ASSBs with zero-excess Li metal anodes (also called anode-free Li metal batteries) have been proposed; various cell designs have been developed to overcome the limitations of lithium metal anodes; the limitations include the low Coulombic efficiency, dendrite growth, and high production cost. [25][26][27] Recently, Lee et al reported that an all-solid-state lithium metal battery with a sulfide-based solid electrolyte and an Ag-C composite anode exhibited a high energy density (> 900 Wh⋅L −1 ) and Coulombic efficiency (> 99.8%). 28 The Ag-C nanocomposite layer was crucial in ensuring a dense, uniform, and dendrite-free plating of Li metal.…”
Section: Introductionmentioning
confidence: 99%
“…ASSBs with zero‐excess Li metal anodes (also called anode‐free Li metal batteries) have been proposed; various cell designs have been developed to overcome the limitations of lithium metal anodes; the limitations include the low Coulombic efficiency, dendrite growth, and high production cost 25–27 . Recently, Lee et al.…”
Section: Introductionmentioning
confidence: 99%